Implementation of the Gayo Cultural Values System as School Culture: Implementation of the Gayo Cultural Values System as School Culture - Mahani, Fitris; Rahmi Novalita, Rahmi Novalita; Fitrah, Hariki (Sumatra Journal of Disaster, Geography and Geography Education, 2024)
This research aims to describe the implementation of the Gayo cultural values ​​system as school culture at Kuta Panang 10 Public Elementary School. This type of research is qualitative research. Research informants are key informants. The informants were the deputy principal, teachers and students of Kuta Panang 10 Public Elementary School. Data collection techniques include observation, interviews and documentation. Data analysis techniques use data reduction, data display, and drawing conclusions. The results of the research show that the Kuta Panang 10 public elementary school has well implemented the Gayo cultural value system as a school culture which consists of; orderly, loyal (setie), affection (semayang–gemasih), hard work (mutentu), trustworthy, deliberative (genap mupakat), mutually helpful (alang tulung) and competitive (bersikekemelen).